2010
DOI: 10.1002/bit.22699
|View full text |Cite
|
Sign up to set email alerts
|

Identification and prevention of antibody disulfide bond reduction during cell culture manufacturing

Abstract: In the biopharmaceutical industry, therapeutic monoclonal antibodies are primarily produced in mammalian cell culture systems. During the scale-up of a monoclonal antibody production process, we observed excessive mechanical cell shear as well as significant reduction of the antibody's interchain disulfide bonds during harvest operations. This antibody reduction event was catastrophic as the product failed to meet the drug substance specifications and the bulk product was lost. Subsequent laboratory studies ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(145 citation statements)
references
References 23 publications
3
142
0
Order By: Relevance
“…L‐cystine was reported to be a potential competitive inhibitor of the reducing enzymes or to act as a surrogate substrate for the enzyme in place of the mAb product (Trexler‐Schmidt et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…L‐cystine was reported to be a potential competitive inhibitor of the reducing enzymes or to act as a surrogate substrate for the enzyme in place of the mAb product (Trexler‐Schmidt et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…They hypothesized that the mechanical forces in the centrifuge were responsible for reducing the molecule into half‐antibodies (Hutchinson et al, 2006). Trexler‐Schmidt and co‐workers further demonstrated that antibody disulfide reduction can be attributed to the cell lysis and the release of intra‐cellular reducing enzymes (primarily thio‐redoxin reductase/thioredoxin) as a result of harsh centrifugation conditions (Trexler‐Schmidt et al, 2010). Hutterer and co‐workers attributed the extent of antibody reduction to be dependent on the cell line and cell culture process (Hutterer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have published extensive reviews, depicting the current state of the art and strategies, which focus on the cell line 1,7,16,45 and the cell culture parameters 18,51 . Furthermore, through the concentration adjustment of selected media components, and in some cases by supplementing the medium with specific co-factors, it is possible to adjust the glycosylation profile 52 , the charge variants 53 , the aggregation level 46,54 , and the abundance of LMW species 55 . Figure 1.1 outlines the three main strategies allowing to affect cell culture process performance and to tailor the quality attributes of therapeutic molecules.…”
Section: Cell Culture Process Optimizationmentioning
confidence: 99%
“…Dehydroepiandrosterone, epiandrosterone, pyridoxal 5'-phosphate, 1-fluoro-2,4-dinitrobenzene have effectively reduced G6PD activity and the addition of chelating agents (EDTA & EGTA), citrate, distinct types of phosphates, 6-deoxy-6-fluoroglucose, 2-C-hydroxy-methylglucose, xylose, or lyxose inhibit hexokinase 186 . L-cystine exhibited chemical inhibitory capacities for a recombinant monoclonal antibody due to its function as competitive inhibitor for reducing enzymes 55 . A mixture of protease inhibitors including E64, leupeptin, benzamidine, E-amino caproic acid, pepstatin A, and EDTA was tested.…”
Section: Low-molecular-weight Speciesmentioning
confidence: 99%